Republic of Armenia : Accumulation, Competition, and Connectivity - World Bank (Washington, DC, 2014)
By 2013, the Armenian economy has left behind most of the hangover from the global financial crisis and a look at medium- to long-term growth drivers is therefore in order. The central tenet of this report is that the government's job creation agenda requires a different growth model than the one followed before the global crisis. Reaching the goals of the government's strategy will require a combination of four factors: first, higher investment and better financial intermediation between savers and investors. Second, better utilization of the labor force, including the largely untapped resource of Armenians abroad. Third, stronger competitive pressures in the markets for goods and services, which will improve incentives for companies to innovate, adopt new technologies, and become more efficient. Fourth, enhanced connections of the landlocked Armenian economy with world markets, including through land, air, and through internet and communication technologies. This report's theoretical framework emphasizes structural reforms to drive growth. This report is structured as follows: chapter one is macroeconomic developments and outlook; chapter two focuses on saving, investment, and financial intermediation; chapter three focuses on human resources; chapter four focuses on competition; chapter five focuses on land connectivity; chapter six focuses on air connectivity; and chapter seven deals with internet and communications technology (ICT).